Targeting prostate cancer by new bispecific monocyte engager directed to prostate-specific membrane antigen - Gargi Das; Jakub Ptacek; Jana Campbell; Xintang Li; Barbora Havlinova; Satish kumar Noonepalle; Alejandro Villagra; Cyril Barinka; Zora Novakova (PLoS ONE, 2025)
Prostate cancer (PCa) ranks as the second leading cause of cancer-related deaths among men in the United States. Prostate-specific membrane antigen (PSMA) represents a well-established biomarker of PCa, and its levels correlate positively with the disease progression, culminating at the stage of metastatic castration-resistant prostate cancer. Due to its tissue-specific expression and cell surface localization, PSMA shows superior potential for precise imaging and therapy of PCa. Antibody-based immunotherapy targeting PSMA offers the promise of selectively engaging the host immune system with minimal off-target effects. Here we report on the design, expression, purification, and characterization of a bispecific engager, termed 5D3-CP33, that efficiently recruits macrophages to the vicinity of PSMA-positive cancer cells mediating PCa death. The engager was engineered by fusing the anti-PSMA 5D3 antibody fragment to a cyclic peptide 33 (CP33), selectively binding the Fc gamma receptor I (FcγRI/CD64) on the surface of phagocytes. Functional parts of the 5D3-CP33 engager revealed a nanomolar affinity for PSMA and FcγRI/CD64 with dissociation constants of K D =  3 nM and K D =  140 nM, respectively. At a concentration as low as 0.3 nM, the engager was found to trigger the production of reactive oxygen species by U937 monocytic cells in the presence of PSMA-positive cells. Moreover, flow cytometry analysis demonstrated antibody-dependent cell-mediated phagocytosis of PSMA-positive cancer cells by U937 monocytes when exposed to 0.15 nM 5D3-CP33. Our findings illustrate that 5D3-CP33 effectively and specifically activates monocytes upon PSMA-positive target engagement, resulting in the elimination of tumor cells. The 5D3-CP33 engager can thus serve as a promising lead for developing new immunotherapy tools for the efficient treatment of PCa.